2004
DOI: 10.1177/112067210401400508
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure, Safety and Quality of Life in Glaucoma Patients Switching to Latanoprost from Adjunctive and Monotherapy Treatments

Abstract: In a clinical setting, patients who have their mono- and adjunctive therapy treatment substituted for latanoprost may on average experience reduced IOP, decreased side effects and increased quality of life measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 14 publications
0
8
1
1
Order By: Relevance
“…These data are seemingly inconsistent, however, with those of previous studies which showed switching patients from DTFC to latanoprost also provided a decrease in pressure (Zimmerman & Stewart 2003;Bayer et al 2004;Haverkamp et al 2004;Hamacher et al 2004). The reason why patients would have further reductions in pressure depending on the order in which the medicines were prescribed is not clear, but it may be based on several potential mechanisms: firstly, patients may have a true increase in efficacy with the new medication.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…These data are seemingly inconsistent, however, with those of previous studies which showed switching patients from DTFC to latanoprost also provided a decrease in pressure (Zimmerman & Stewart 2003;Bayer et al 2004;Haverkamp et al 2004;Hamacher et al 2004). The reason why patients would have further reductions in pressure depending on the order in which the medicines were prescribed is not clear, but it may be based on several potential mechanisms: firstly, patients may have a true increase in efficacy with the new medication.…”
Section: Discussioncontrasting
confidence: 53%
“…Trials in the USA and Germany have shown generally that patients on other mono-and adjunctive therapies, including DTFC, experienced a further statistical reduction in IOP when they switched to latanoprost or latanoprost ⁄ timolol fixed combination (Zimmerman & Stewart 2003;Bayer et al 2004;Haverkamp et al 2004;Hamacher et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Long-term use of topical ocular drugs is often associated with ocular inflammation, allergy, dry eye syndrome, and failure of filtration surgery. [2][3][4][5][6][7][8] Several lines of evidence indicate that these agents are associated with decreased tear turnover and tear film break-up time, infiltration of the conjunctiva by inflammatory cells and fibroblasts, and overexpression of inflammatory markers such as HLA-DR, intercellular adhesion molecule (ICAM-1), FAS antigen, or the apoptotic marker Apo 2.7. 9 -14 The preservative benzalkonium chloride (BAK), the most commonly used ocular preservative, is largely responsible for the ocular toxicities and inflammation associated with the chronic use of many ophthalmic solutions.…”
mentioning
confidence: 99%
“…periocular dermatitis -as Baudouin refers, 20 in addition to allergic conjunctivitis, (which rarely corresponds to type i hypersensitivity) the most frequent drug-induced allergic reaction is a type iV delayed cell-mediated hypersensitivity. this could explain why many reactions occur at the eyelid level, (such as allergic blepharitis) which are often difficult to distinguish from other causes of eyelid inflammation or contact dermatitis (see Figure 3).…”
Section: Preservatives and Effectsmentioning
confidence: 99%